Evaluation of Human Exposure to Aedes Bites in Rubber and Palm Cultivations Using an Immunoepidemiological Biomarker. (9th August 2018) - Yobo, Céline Mabot; Sadia-Kacou, Cécile Agnimou Malanfoua; Adja, Maurice Akré; Elanga-Ndille, Emmanuel; Sagna, André Barembaye; Guindo-Coulibaly, Négnorogo; Poinsignon, Anne; Remoue, Franck; Koudou, Benjamin Guibéhi
Abstract : Arbovirus infections, mainly transmitted by Aedes mosquito, are emerging in Africa. Efficient vector control requires an understanding of ecological factors which could impact on the risk of transmission, such as environmental changes linked to agricultural practices. The present study aims to assess the level of human exposure to Aedes mosquito bites in different agroecosystem area, using an immunological tool which quantifies human IgG antibody response to one Ae. aegypti salivary peptide. Specific IgG responses were assessed during dry and rainy seasons, in children living in different villages in Côte d'Ivoire: N'Zikro (rubber and oil palm exploitations), Ehania-V5 (oil palm), and Ayébo (without intensive agricultural activities). In the dry season, specific IgG levels were significantly lower in Ayébo compared to Ehania-V5 and N'Zikro and, interestingly, were similarly high in both villages with cultivations. In the rainy season, no difference of specific IgG was observed between villages. Specific IgG responses remained therefore high during both seasons in villages associated with intensive agricultural. The rubber and oil palm cultivations could maintain a high level of human exposure to Aedes mosquito bites during both dry and rainy seasons. These agricultural activities could represent a permanent risk factor of the transmission of arboviruses.